(untitled) - Kottegoda, Nathabandu T (New York, 1997)
This books consists of the following many parts such as: preliminary data analysis, basic probability concepts, radom variables and their properties, probability distributions, model estimation and testing.
Keywords: Civil engineering,Environmental engineering,Probabilities,Reliability ( engineering ); Statistical methods,Statistical methods